Membrane tension controls the phase equilibrium in fusogenic liposomes. Issue 37 (24th August 2022) - Schmitt, Laura Maria; Dreissen, Georg; Kolasinac, Rejhana; Csiszár, Agnes; Merkel, Rudolf
Abstract : The lipid moiety of fusogenic liposomes is in a mixed phase state whose thermodynamic equilibrium depends on membrane tension. Abstract : Fusogenic liposomes have been widely used for molecule delivery to cell membranes and cell interior. However, their physicochemical state is still little understood. We tested mechanical material behavior by micropipette aspiration of giant vesicles from fusogenic lipid mixtures and found that the membranes of these vesicles are fluid and under high mechanical tension even before aspiration. Based on this result, we developed a theoretical framework to determine the area expansion modulus and membrane tension of such pre-tensed vesicles from aspiration experiments. Surprisingly high membrane tension of 2.1 mN m −1 and very low area expansion modulus of 63 mN m −1 were found. We interpret these peculiar material properties as the result of a mechanically driven phase transition between the usual lamellar phase and an, as of now, not finally determined three dimensional phase of the lipid mixture. The free enthalpy of transition between these phases is very low, i.e. on the order of the thermal energy.